CT-Based Defect Analysis in Aluminium Rotor End Rings - István Kozma; Ibolya Zsoldos (Engineering Proceedings)
The advantages of using cast aluminium rotors have been proven recently. However, discontinuities and porosities created during the casting of aluminium can cause problems during motor operation, such as eccentricity, losses, unwanted sounds, and false rotor fault indications. During the casting technology, care must be taken to ensure that there are as few cracks and porosities as possible in the volume and that their distribution is homogeneous. In this article, we present in detail the application of the modern CT-based methodology that has been spreading recently for the detection and analysis of discontinuities, voids, and porosities created during the casting of rotor end rings.